Influence of the irradiated pulmonary microenvironment on macrophage and T cell dynamics - Groves, Angela M.; Misra, Ravi; Clair, Geremy; Hernady, Eric; Olson, Heather M.; Orton, Daniel J.; Finkelstein, Jacob N.; Marples, Brian; Johnston, Carl J. (Radiotherapy and oncology, 2023)
The lung is sensitive to radiation, which increases the risk of normal tissue toxicity following radiation therapy. Adverse outcomes include pneumonitis and pulmonary fibrosis, which are thought to result from dysregulated intercellular communication within the pulmonary microenvironment. Macrophage accumulation in the lung following radiation exposure is implicated in these pathogenic outcomes. Here we investigate the role of the microenvironment in macrophage and T cell dynamics. Materials and methods C57Bl/6 mice received 6Gyx5 x-ray irradiation to the right lung. Macrophage and T cell dynamics were investigated in ipsilateral right lungs, contralateral left lungs and compared to those from non-irradiated control subjects at 4-26wk post exposure. Lungs were evaluated by flow cytometry, histology and proteomics. Results In uni-lung irradiated subjects, focal regions of macrophage accumulation were noted in both lungs by 8wk, however fibrotic lesions were observed only in ipsilateral lungs by 26wk. Both infiltrating and alveolar macrophages populations transiently expanded in both lungs, however a transitional CD11b+ alveolar macrophage population persisted only in ipsilateral lungs and expressed lower CD206. Concurrently, arginase-1+ macrophages were noted within areas of macrophage accumulation in ipsilateral but not contralateral lungs at 8 and 26wk post exposure, while CD206+ macrophages were absent from these accumulations. While CD8+ T cells were present in both lungs of irradiated subjects, T regulatory cells were only increased in ipsilateral lungs. Unbiased proteomics analysis of immune cells revealed a substantial number of differentially expressed proteins in ipsilateral lungs when compared to either contralateral or non-irradiated lungs, as well as between contralateral lungs from irradiated subjects and non-irradiated controls. Conclusions Pulmonary macrophage and T cell dynamics are impacted by the microenvironmental conditions that develop in the lung following radiation exposure, both locally and systemically. Our findings demonstrate that while macrophages and T cells infiltrate and expand in both lungs, they diverge phenotypically depending on their environment.